Analisis Keterampilan Berbicara Bahasa Jawa Peserta Didik Sekolah Dasar dalam Perspektif Sosiolinguistik - Namira Shifa Chaerunnisa; Joko Daryanto; Septi Yulisetiani (Universitas Sebelas Maret, 2026)
This study aimed to analyze students' Javanese speaking skills and the factors influencing them from a sociolinguistic perspective. This study employed a qualitative method with a case study approach. Data collection techniques included observation, interviews, and documentation. Data analysis was conducted using the interactive analysis model developed by Miles and Huberman. The results showed that students' Javanese speaking skills had not yet demonstrated optimal application of unggah-ungguh basa (Javanese speech etiquette). Students were able to use the ngoko (informal) register in interactions with peers; however, they were not yet able to use the krama (formal) register consistently in formal situations. In addition, the use of Indonesian and code-mixing was found when communicating with teachers. This condition was influenced by internal factors, namely limited krama vocabulary and low self-confidence, as well as external factors, namely insufficient habituation in the use of krama within the family and school environments and the dominance of Indonesian. From a sociolinguistic perspective, these findings indicate that students had not yet been able to adjust their language use according to the social context of communication.